Comprehensive assessment of tert mRNA expression across a large cohort of benign and malignant thyroid tumours - Pestana, A (2020)
The presence of TERT promoter (TERTp) mutations in thyroid cancer have been associated with worse prognosis features, whereas the extent and meaning of the expression and activation of TERT in thyroid tumours is still largely unknown. We analysed frozen samples from a series of benign and malignant thyroid tumours, displaying non-aggressive features and low mutational burden in order to evaluate the presence of TERTp mutations and TERT mRNA expression in these settings. In this series, TERTp mutations were found in 2%, only in malignant cases, in larger cancers, and from older patients. TERT mRNA expression was detected in both benign and malignant tumours, with increased frequencies in the malignant tumours with aggressive histotypes, larger tumours, and from older patients. In benign tumours, TERT mRNA expression was found in 17% of the follicular thyroid adenoma (FTA) with increased levels of expression in smaller tumours and associated with the presence of thyroiditis. TERTp mutations and TERT mRNA expression are correlated with worse prognosis features in malignant thyroid tumours, whereas TERT mRNA expression in the benign tumours is associated with the presence of thyroiditis.